Analisis Produk Cacat pada Block Beton Menggunakan Metode Seven Tools dan Failure Mode Effect Analysis di Perusahan Precast XYZ - Hady Sofyan; Regyawan Maydi Syafei Putra; IndraGumelar; Tarman; Farliana Sutartiah (JURNAL TEKNOSAINS KODEPENA, 2024)
XYZ Company is a company in the manufacturing sector of precast concrete production, ready-to-use concrete products to meet the needs of the construction industry. The problem in this company is that there are still many defects that occur in the concrete produced. The purpose of this study is to find out what defects occur in concrete blocks, analyze the causes of their occurrence and make repair suggestions. This study uses the seven basic tools method to analyze the types of defects and the causes of defects in concrete blocks, and the FMEA method to make repair recommendations with the cause of defects from the highest RPN value. Based on the results of data processing, there are several defects that occur in concrete blocks, namely: porous, small cracks, non-angled products, non-uniform colors, bubbles, dimensions, gripis, and hairline cracks. From the Fishbone results, there are 18 indicators of the causes of the three defects, from the 18 causes of defects, the RPN value is then determined with the highest RPN value of 168, namely dirty, leaking, and less tight mold indicators..